2016
DOI: 10.1128/aac.00276-16
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Inhibition of VanA byd-Alanine Reduces Vancomycin Resistance in a VanX-Dependent Manner

Abstract: Infectious diseases caused by multidrug-resistant (MDR) pathogens are spreading rapidly and are among the biggest threats to human health (1-4). A particular problem with drug discovery from microbial sources is the high frequency of rediscovery of known compounds, which necessitates new approaches to replenish the antimicrobial drug pipelines (5-7). To deal with the increasing antibiotic resistance, novel antibiotics are called for, or alternatively, the life spans of the current drugs must be prolonged by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…This result suggests that excess D-lactate presence contributes to synergism phenotype, possibly by resulting in peptidoglycan precursors ending in D-lactate. As expected based on the results of Aart et al [ 29 ], vancomycin MIC decreased in the presence of D-alanine, and we observed only a 2-fold additional MIC decrease in the presence of both D-alanine and H-CHG ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result suggests that excess D-lactate presence contributes to synergism phenotype, possibly by resulting in peptidoglycan precursors ending in D-lactate. As expected based on the results of Aart et al [ 29 ], vancomycin MIC decreased in the presence of D-alanine, and we observed only a 2-fold additional MIC decrease in the presence of both D-alanine and H-CHG ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
“…This increased the efficacy of vancomycin against Streptomyces and E . faecium [ 29 ]. Another study has reported the formation of modified cytoplasmic cell wall precursor termini in the presence of D-hydroxy acids, including D-lactate, and correlation of this with vancomycin resistance levels in Lactobacillus [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the cytoplasmic PG precursor isolation and identification, we used a modification of the method previously described ( 61 ). The alpha strain and the divIVA and dcw mutants were grown in LPB for 7 days, while the wild-type K. viridifaciens strain was grown for 3 days in a modified version of LPB lacking sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that bacterial PG dipeptide D-Ala-D-Ala, which is generated by D-Ala-D-Ala ligase ( ddlA ), is the usual target for vancomycin, but in C. jejuni, PG contains D-Alanyl-D-Lactate (D-Ala-D-Lac) termini resulting in reduced efficacy of vancomycin by up to 1000-fold. Substitution by D -alanyl- D -serine (D-Ala-D-ser) termini reduces the efficacy of this antibiotic by up to 7-fold [ 4 , 55 , 56 , 57 , 58 ]. This further suggests that alr and not ddlA, is likely to be the primary target for D-ser and DCS in C. jejuni .…”
Section: Discussionmentioning
confidence: 99%